A Systematic Review of Psychological and Sociological Factors in Arabic Language Learning among Foreign Speakers in Indonesia - Maharani, Ninda; Zalni, Nurfitri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study systematically reviews 25 empirical articles published between 2019 and 2025 to comprehensively examine the role of psychological and sociological factors in Arabic language learning among foreign speakers in Indonesia, particularly by elucidating the dynamics of language anxiety, learning motivation, and self-efficacy within the social context of learning. This study employs a systematic literature review following PRISMA guidelines, analyzing scientific articles obtained from the Scopus, DOAJ, SINTA, and Google Scholar databases. Thematic analysis was used to identify patterns and correlations between psychological and sociological variables. The results of the study show that speaking anxiety emerges as a significant obstacle to communicative participation, while motivation and self-efficacy play a role in maintaining the sustainability of student learning engagement, which is greatly influenced by the quality of the learning environment, support from teachers and peers, and the dynamics of social interaction in the classroom. These findings indicate that students' psychological conditions do not develop individually but are shaped through continuous social learning experiences. Therefore, Arabic language learning should be understood as an integrated socio-affective process, guiding the development of pedagogical practices to create a learning environment that is psychologically safe, communicative, and responsive to students' needs, thereby supporting the development of sustainable language competence.